The Influence of Physical and Non-Physical Work Environment on Job Satisfaction of Civil Servants at the Regional Revenue Agency of Sanggau Regency - Juliyansah Juliyansah; Irfan Mahdi (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to examine the influence of the physical work environment and the non-physical work environment on job satisfaction among employees of the Regional Revenue Agency (Badan Pendapatan Daerah) of Sanggau Regency. This research employs a quantitative approach with an associative research design. A saturated sampling technique was applied, involving 59 employees of the Regional Revenue Agency of Sanggau Regency, consisting of civil servants and contract-based government employees (PPPK), excluding the head of the agency. Data were analyzed using multiple linear regression with SPSS version 25, supported by validity tests, reliability tests, and classical assumption tests. The results indicate that the physical work environment has a positive and significant effect on job satisfaction (t = 2.317; p = 0.024). The non-physical work environment also has a positive and significant effect on job satisfaction, with a stronger influence (t = 5.999; p 0.001). Simultaneously, both the physical and non-physical work environments significantly affect job satisfaction (F = 41.450; p 0.001), with a coefficient of determination (R²) of 0.597. These findings suggest that 59.7% of the variation in job satisfaction can be explained by the physical and non-physical work environments, while the remaining 40.3% is influenced by other factors not included in this study.